Sensor Based Healthcare Model - Shanthi Meesala, Sri; Ramesh Babu, G.V (International Journal of Computer Sciences and Engineering, 2025)
The theme of the work done is to have an SMS text-enabled communication medium between the outsider and the guardian (through GSM communication). At the moment there are many wearables in the market which help track the daily activity of people and also help find the person using Wi-Fi and Bluetooth services present on the device. However, Wi-Fi and Bluetooth appear to be an unreliable medium of communication between the guardian and the person. The guardian can send text with specific keywords like “LOCATION”, “TEMPERATURE”, “HEARTBEAT”, “SOS”, “BUZZER”, and the wearable device will reply you back with a text containing the health conditions and also accurate real-time location of the person which upon tapping will provide directions to the person’s position on Google Maps App and will also give the surroundings temperature. So our project mainly focuses on the basic design and implementation of such devices.The secondary measure taken is the implementation of the bright SOS light and the distress alarm buzzer present on such devices which when activated by the guardian via SMS text displays SOS light brightly and sound an alarm which a bystander can easily spot as a sign of distress.